Analysis Of Work Shift Arrangements At Agung Raya Company - Calvin Kimura; Christian Wiradendi Wolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The purpose of this study is to analyze the shift system used in Agung Raya company, determine its impact on employees and develop strategies to reduce the negative impact of the shift system. This research used a descriptive qualitative approach with observation, interview and written data collection methods. Data were analyzed using interactive analysis techniques and purposive sampling techniques were used to identify informants. The results showed that shift work has a significant impact on employee health and well-being. The shift system implemented has considered aspects such as rest time between shifts, schedule rotatio, and workload management. However, some aspects still need to be optimized to further improve employee well-being. This research provides practical recommendations for companies to manage work shift systems and contributes to the advancement of human resource management research.